Chaos Control and Synchronization via Switched Output Control Strategy. (29th January 2017) - Luo, Runzi; Su, Haipeng; Zeng, Yanhui
Abstract : This paper investigates the control and synchronization of a class of chaotic systems with switched output which is assumed to be switched between the first and the second state variables of chaotic system. Some novel and yet simple criteria for the control and synchronization of a class of chaotic systems are proposed via the switched output. The generalized Lorenz chaotic system is taken as an example to show the feasibility and efficiency of theoretical results.